Maternal HIV Status Associated With Under-Five Mortality in Rural Northern Malawi: A Prospective Cohort Study. (1st January 2015) - Chihana, Menard L.; Price, Alison; Floyd, Sian; Mboma, Sebastian; Mvula, Hazzie; Branson, Keith; Saul, Jacqueline; Zaba, Basia; French, Neil; Crampin, Amelia C.; Glynn, Judith R.
Abstract : Background: Under-five mortality is decreasing but with little change in neonatal mortality rates. We examined the effect of maternal HIV status on under-five mortality and cause of death since widespread availability of antiretroviral therapy in rural Malawi. Methods: Children born in 2006–2011 in the Karonga demographic surveillance area were included. Maternal HIV status was available from HIV serosurveys. Age-specific mortality rate ratios for children born to HIV-positive and HIV-negative mothers were obtained by fitting a Poisson model accounting for child clustering by mother and adjusting for potential confounders. Cause of death was ascertained by verbal autopsy. Findings: There were 352 deaths among 6913 under-five singleton children followed for 20, 754 person-years (py), giving a mortality rate of 17.0/1000 py overall, 218/1000 py (16.5/1000 live births) in neonates, 20/1000 py (17.4/1000 live births) in postneonatal infants, and 8/1000 py in 1–4 years old. Comparing those born to HIV-positive and HIV-negative mothers, the rate ratio adjusted for child age, sex, maternal age, parity, and drinking water source was 1.5 (95% confidence interval [CI]: 0.6 to 3.7) in neonates, 11.5 (95% CI: 7.2 to 18.5) in postneonatal infants, and 4.6 (95% CI: 2.7 to 7.9) in 1–4 years old. Birth injury/asphyxia, neonatal sepsis, and prematurity contributed >70% of neonatal deaths, whereas acute infections, malaria, diarrhea, and pneumonia accounted for most deaths in older children. Conclusions: Maternal HIV status had little effect on neonatal mortality but was associated with much higher mortality in the postneonatal period and among older children. Greater attention to HIV care in pregnant women and mothers should help improve child survival, but broader interventions are needed to reduce neonatal mortality.